2021
DOI: 10.1016/j.parkreldis.2021.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The commercial genetic testing landscape for Parkinson's disease

Abstract: Introduction:There have been no specific guidelines regarding which genes should be tested in the clinical setting for Parkinson's disease (PD) or parkinsonism. We evaluated the types of clinical genetic testing offered for PD as the first step of our gene curation. Methods: The National Institutes of Health (NIH) Genetic Testing Registry (GTR) was queried on 12/7/2020 to identify current commercial PD genetic test offerings by clinical laboratories, internationally. Results: We identified 502 unique clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Most commercial genetic testing panels are largely limited to monogenic causes of familial PD. 18 Moreover, such panels often include genes with limited evidence or omit more recently discovered loci. By contrast, genome sequencing offers more comprehensive genetic analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most commercial genetic testing panels are largely limited to monogenic causes of familial PD. 18 Moreover, such panels often include genes with limited evidence or omit more recently discovered loci. By contrast, genome sequencing offers more comprehensive genetic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The available tests also vary widely in the number of genes and variants tested, frequently include loci with uncertain evidence, and do not include common genetic variants or assess a genetic risk score. 18 Compared with targeted panel assays, genome sequencing comprehensively examines both rare and common variants in most genes. In addition, results can be readily filtered and reported based on all available evidence, making possible iterative analytic updates following new discoveries and without requiring an additional blood draw or new data generation.…”
mentioning
confidence: 99%
“…A recent study evaluated the types of clinical genetic tests that are used in PD, revealing notable differences in gene panel size, ranging from 5 to 62 genes. That study showed that five genes were included in all panels ( SNCA , PRKN , PINK1 , PARK7 ( DJ1 ), and LRRK2 ), while VPS35 and GBA were only variably included, and that the differences between panels were mainly the result of the variable inclusion of genes associated with atypical parkinsonism and dystonia disorders, or genes with an uncertain association with PD [ 139 ]. The selected gene panel should ideally include all established genes for PD with both sequence and deletion/duplication analysis.…”
Section: Genetic Testing In Parkinson’s Diseasementioning
confidence: 99%
“…Notable limitations that should be taken into consideration are the ones associated with the GBA gene, for which a related pseudogene and structural variations may complicate the detection of pathogenic variants. A novel approach is to use long-read sequencing to assess this gene, with the GridION nanopore sequencing platform recently used in a New Zealand cohort of patients [ 139 ]. Another factor to consider is the cost of genetic tests, which might not be covered by the patient’s insurance and therefore may inevitably affect decisions in the molecular workup in some cases.…”
Section: Genetic Testing In Parkinson’s Diseasementioning
confidence: 99%
“…10 Various commercial laboratories offer different PD panels that look for mutations among the 5 to 62 genes associated with an increased risk of PD. 19 Most of these panels include the seven genes mentioned above. In addition to mendelian inheritance, many single-nucleotide polymorphisms (SNPs) are associated with a mildly increased risk of PD; combined, these may have a significant role in the development of PD.…”
Section: Risk Factorsmentioning
confidence: 99%